Hunter-gatherer genetic persistence at the onset of megalithism in western Iberia: New mitochondrial evidence from Mesolithic and Neolithic necropolises in central-southern Portugal - Carvalho, AF (2023)
Despite its strategic importance at the furthermost edge of the Neolithic expansion in Europe, archaeogenetic data from Mesolithic and Neolithic human remains from Portugal are still very limited. Here we present ancient mtDNA evidence (mostly unpublished) to fill the gap and discuss the pattern of "genetic resurgence" of huntergatherer (Mesolithic) ancestry, widely reported elsewhere in Europe, among the first megalith builders (Middle Neolithic) of western Iberia.A total of 11 Mesolithic and Neolithic necropolises located in the central and southern regions of Portugal dated to ca. 6200-3000 BC were studied. These sites comprise all Mesolithic-Neolithic cultural stages and include several funerary architectures and spaces. Reproducible mtDNA HVRI haplotypes were obtained from 23 individuals from six different archaeological sites spread across a >3000-year transect, from the Late Mesolithic to the Late Neolithic.Our results support a three-stage explanatory demographic and populational model: i) local hunter-gatherer populations constituted a highly homogeneous genetic pool; ii) the first farming practices were introduced by human groups carrying new, extraneous haplogroups and exhibiting the signature of admixture events occurring at the time of first contact with local hunter-gatherers; iii) the genetic pattern detected among the megalithbuilding populations, showing hunter-gatherer along with farming ancestry, may be explained by the segmentary principles, and attendant endogamic practices, that structured Neolithic societies.